On the Ricardian Invariable Measure of Value in General Convex Economies: Applicability of the Standard Commodity - Kazuhiro Kurose; Naoki Yoshihara (University of Massachusetts, Department of Economics, 2013)
The purpose of this paper is to examine the critical arguments made by Burmeis- ter, Samuelson, and others, with respect to Sraffa (1960). Sraffa did not address these arguments, but they are relevant from the viewpoint of modern economic theories. In his arguments about the standard commodity, Sraffa assumed that a change in in- come distribution has no effect on the output level and choice of techniques. However, modern economic theories allow interdependence among changes in income distribu- tion, output level, and choice of techniques. Therefore, it is interesting to consider the existence of an invariable measure of value and linearity of income distribution in a model where such interdependence is discussed. We assume general convex economies with non-increasing returns to scale. In this model, we obtain the conditions under which the existence of an invariable measure of value and the validity of the linearity of income distribution are assured.
Keywords: B51; D30; D51; 330; Ricardo's invariable measure of value; Sraffa's standard commodity; General convex economies; Linear relation of income distri- bution